The Preparation of Control Blood for External Quality Assessment Programs in Oral Anticoagulant Control - van Dijk-Wierda, C A; van Halem-Visser, L P; van der Hoeff-van Halem, R; Loeliger, E A (Thrombosis and Haemostasis, 1978)
A method is described for the preparation of blood samples differing in coagulability, now used for external quality control in The Netherlands by laboratories employing thrombotest for the assessment of oral anticoagulant agents.